2017
DOI: 10.1080/1059924x.2017.1318100
|View full text |Cite
|
Sign up to set email alerts
|

Hydration and Cooling Practices Among Farmworkers in Oregon and Washington

Abstract: Objectives Although recommendations for preventing occupational heat-related illness among farmworkers include hydration and cooling practices, the extent to which these recommendations are universally practiced is unknown. The objective of this analysis was to compare hydration and cooling practices between farmworkers in Oregon and Washington. Methods A survey was administered to a purposive sample of Oregon and Washington farmworkers. Data collected included demographics, work history and current work pra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 16 publications
2
16
0
Order By: Relevance
“…We also noted the use of salt tablets among younger workers that we have previously documented (Culp et al, 2011). Our finding that workers in the CS group were consuming beverages high in caffeine and sugar is consistent with others (Bethel, Spector, & Krenz, 2017). One study of HFs found that the consumption of caffeinated drinks may be related to a desire to stay alert and that the consumption of soft drinks may have been related to on-site water quality (Lam et al, 2013).…”
Section: Discussionsupporting
confidence: 93%
“…We also noted the use of salt tablets among younger workers that we have previously documented (Culp et al, 2011). Our finding that workers in the CS group were consuming beverages high in caffeine and sugar is consistent with others (Bethel, Spector, & Krenz, 2017). One study of HFs found that the consumption of caffeinated drinks may be related to a desire to stay alert and that the consumption of soft drinks may have been related to on-site water quality (Lam et al, 2013).…”
Section: Discussionsupporting
confidence: 93%
“…Reported consumption in this study is nearly a liter less than what NIOSH recommends. These findings are echoed in other studies of agricultural workers in the United States (Bethel, Spector, & Krenz, 2017; Lam et al, 2013; Mix et al, 2018). Due to the importance of maintaining hydration while working in the heat, this represents an area for a potential health intervention and improved worker education as part of trainings to prevent heat‐related illness.…”
Section: Discussionsupporting
confidence: 55%
“…In a study of kidney function in agricultural workers in Florida, Mix and colleagues (2018) reported the types of beverages workers drink during the day, with water and sports drinks being the most often consumed. Similarly, in a comparison of workers in Oregon and Washington states, Bethel, Spector, and Krenz (2017) reported that workers predominantly drink water, followed by energy drinks and soda.…”
mentioning
confidence: 94%
“…23 Farmworkers discussed wearing long sleeve shirts, pants, and caps, which has been reported in other HRI studies with farmworkers. 24,25 In one North Carolina study, the majority of farmworkers reported wearing protective clothing to reduce sun exposure. 25 However, in another North Carolina study, there was an association between the number of years of experience in farmwork and decreased use of protective clothing, suggesting the need for training refresher courses according to the study authors.…”
Section: Discussionmentioning
confidence: 99%
“…24,25 In one North Carolina study, the majority of farmworkers reported wearing protective clothing to reduce sun exposure. 25 However, in another North Carolina study, there was an association between the number of years of experience in farmwork and decreased use of protective clothing, suggesting the need for training refresher courses according to the study authors. 26 Based on these results, the research identified some potential gaps in heat safety education.…”
Section: Discussionmentioning
confidence: 99%